2022
DOI: 10.20884/1.jm.2022.17.1.5600
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking of Xanthone Derivatives as Therapeutic Agent for Covid-19

Abstract: Covid-19 has caused more than 14 million confirmed cases and more than 6 hundred deaths as of 21 July 2020 globally. However, there is no approved drug to treat the disease. Xanthone is a potential therapeutic option for the virus that have been tested using molecular docking. There were 12 of xanthone compounds and its derivatives which have been docked against two protein crystals, 2GX4.pdb and 6FV1.pdb, which obtained two potential compounds of hydroxyxanthone derivatives with sulfonate and chloro substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Numerous natural compounds inhibit the SARS-CoV-2 main protease (M pro ) 4 , including flavonoids 5 , 6 , phenolics 7 , 8 , and xanthones 9 . Xanthones such as mangostins and their derivatives are major compounds isolated from mangosteen, which is a fruit widely used in folk medicine in tropical countries.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous natural compounds inhibit the SARS-CoV-2 main protease (M pro ) 4 , including flavonoids 5 , 6 , phenolics 7 , 8 , and xanthones 9 . Xanthones such as mangostins and their derivatives are major compounds isolated from mangosteen, which is a fruit widely used in folk medicine in tropical countries.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, studied by Yuanita et al. (2019, 2021) found that adding a chloro substituent to hydroxyxanthone derivatives enhanced anticancer activity against T47D and HeLa cancer cells, and the addition of a bromo substituent improved efficacy against P388 cancer cells [12,13] …”
Section: Introductionmentioning
confidence: 99%
“…Yuanita, et al. in 2021 succeeded in conducting the bromination reaction in hydroxyxanthone derivatives using Br 2 in acetic acid [13] …”
Section: Introductionmentioning
confidence: 99%
“…QSPR models are mathematical models relating chemical structure to various physicochemical and physical properties. Many research studies have been conducted in this area in recent years [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Numerous published QSAR and QSPR models include lipophilicity parameters obtained by thin-layer chromatography and highperformance liquid chromatography in a reversed phase system, i.e., RP-TLC or RP-HPLC as R MW and logk w values, respectively or using computational approaches in the form of logP [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%